Epidemiology of lung cancer. - Kollarova, Helena; Janout, Vladimir; Cizek, Ludek (Biomedical papers, 2002)
This review article presents lung cancer epidemiology, describing main epidemiologic characteristics including epidemiological situation in cancer incidence, mortality and survival in Europe in comparison with situation in the Czech Republic. Influence of environmental and life style risk factors like smoking, passive smoking, risk factors of work environment, ionizing radiation, air pollution, nutrition and genetic and hormonal factors are discussed.
Keywords: Lung cancer / Epidemiology / Risk factors